Nd:YAG laser on dental enamel in the reduction of artificial caries demineralization - Zezell, Denise M.; Silva, Mateus R. [UNESP]; Castro, Pedro A. A.; Silva, Tânia M. [UNESP]; Goncalves, Sergio E. P. [UNESP] (My University, 2019)
Nd:YAG-laser associated to a photoabsorber, in the reduction of artificial caries in enamel was evaluated. Eighty bovine specimens with 6mm diameter and 2mm high were obtained and a half of the surface of each was protected as a control. Microdurometer and FTIR were performed initially and 8 groups (n=10) were obtained according to treatments: G1(- control): no-treatment; G2(+control): fluorophosphate; G3(Nd:YAG 60mJ/pulse, 10Hz, 48J/cm2, non-contact); G4(photoabsorber + Nd:YAG 60mJ); G5(Nd:YAG 80mJ/pulse, 10Hz, 64J/cm2); G6(photoabsorber + Nd:YAG 80mJ); G7(Nd:YAG 100mJ/pulse, 10Hz, 80J/cm2); G8(photoabsorber + Nd:YAG 100mJ). De-remineralization cycle were performed for induction of artificial caries and to interferometer, microdurometer and FTIR. Microhardness data were submitted to 2-way ANOVA and Tukey/Dunnett tests 5%. Statistically differences were obtained in the photoabsorberfactor individually and in the interaction between laser and photoabsorber. There was a lower percentage of microhardness loss in the groups with photoabsorber; G8 presented microhardness similar to G2. FTIR data were submitted to T-test 5%. Compared with G2, higher concentrations of carbonate were found in G4, G6 and G8; phosphate in G8; lower Amide-I concentration at G8 and higher Carbonate/Phosphate ratio at G4 and G6. The interferometry results were submitted to 3-way ANOVA of repeated measures 5%. There were statistically differences in the photoabsorber-factor individually and in the time-factor. Photoabsorber decreased the demineralization; Nd:YAG-laser without photoabsorber were less effective than fluoride; Nd:YAG-laser 100mJ with photoabsorber was as effective as fluoride and; the Nd:YAG-laser, associated or not to the photoabsorber, was no more effective than fluoride in the reduction of artificial decay.
Keywords: Caries; Demineralization; Enamel; Laser; Photoabsorber